Bisnis Dalam Perspektif Islam (Telaah Konsep, Prinsip dan Landasan Normatif) - Norvadewi Norvadewi (Al-Tijary, 2015)
Business with all that stuff going on in people's lives every day widely. Many businesses and the variety of motifs and business orientation as well as the increasing complexity of business problems, sometimes making businesses stuck to try anything to achieve its goal, especially if the goal is only for profit and profit alone. So frequent negative actions, which eventually becomes a habit in business behavior. If so, it is not uncommon for businesses identified with the dirty deed, because there are behaviors lying, treasonous, broken promises, deception and deceiving others. This article describes the business in the Islamic approach that includes the Islamic business concept, the principles of Islamic business and normative foundation of Islamic business. Islamic business must be based on Islamic ethics derived from the Qur'an and the Sunnah of the Prophet Muhammad. Generally, business ethics is a normative discipline, whereby particular ethical standards are formulated and then applied. It makes specific judgments about what is right or wrong, which is to say, it makes claims about what ought to be done or what ought not to be done.